Video Game Engagement and Academic Performance: A Correlation Analysis Approach - Nurmarni Athirah Abdul Wahid; Nurul Nadiya Abu Hassan (Randwick International of Social Science Journal, 2023)
Playing video games is a popular leisure activity among adolescents and youths. People's motivations for playing video games, as well as the potential benefits and drawbacks, are an issue of continual debate. Some researchers believed that playing video games negatively impacted academic achievement among students. Consequently, the purpose of this analytical paper is to identify the link between the academic performance of UiTM Pahang Branch, Jengka Campus students and the amount of time they devote to video games. A survey was distributed online in order to collect information regarding the amount of time students spend playing video games and their academic performance. The sample for the study was comprised of 103 students from UiTM Jengka, Pahang, who were chosen at random. This study indicates that there is a statistically significant correlation between the amount of time students spend playing video games and their academic performance at UiTM Jengka, Pahang. The findings reveal that gaming time accounts for 3.72 percent of the total variation in academic achievement, while the remaining 96.28 percent can be attributed to other variables. Moreover, the outcomes show that students who play video games have substantially lower CGPAs compared to students who don't engage in video games. In order to reduce the prevalence of online gaming addiction in the future, this study suggests that awareness campaigns on the adverse consequences of online gaming should be strengthened.